A study on the shear strength and dry-wet cracking behaviour of waste fibre-reinforced expansive soil - Zhen Huang; Huai-Yuan Sun; Yi-Ming Dai; Peng-Bo Hou; Wei-Zheng Zhou; Lin-Lin Bian (Case Studies in Construction Materials, 2022)
Expansive soils have typical expansion and contraction properties. Under the action of dry-wet cycles, the mechanical properties and cracking behaviour of expansive soil change significantly due to repeated expansion and contraction, which results in engineering problems in expansive soil areas. The resource utilization of solid waste in civil engineering is in line with environmental protection policies and is an important solution to engineering problems. In this study, two types of fibres that can be recycled from solid waste are selected: glass fibre (GF) and polypropylene fibre (PF). Through indoor shear strength and dry-wet cracking tests, the influence of fibre content on the shear strength parameters of expansive soil is quantitatively analysed, the enhancement effect of fibres on the crack resistance of expansive soil is evaluated, and the crack characteristics of fibre-reinforced expansive soil as a function of different drying times, numbers of dry-wet cycles and soil layer thicknesses are explored. The results show that both fibre types significantly enhance the shear properties of expansive soils, and types of fibre-reinforced soil exhibit a peak in shear strength parameters at a certain fibre content. Fibre reinforcement inhabits expansive soil cracking to some extent, and both fibre types exhibit the best crack inhibition effect at a fibre content of 0.5%. The fundamental factor controlling the performance of fibre-improved expansive soil is the adhesion of the expansive soil particles to the fibres, and the PF surfaces are much rougher than the GF surfaces, which can further facilitate the interactions between the fibres and soil grains. In general, the improvement effect of PF is better than that of GF.